A meta-analysis of self-reported anticipatory and consummatory pleasure in the schizophrenia-spectrum. (February 2020) - Visser, Katherine Frost; Chapman, Hannah C.; Ruiz, Ivan; Raugh, Ian M.; Strauss, Gregory P.
Abstract: Objective: Recent conceptual frameworks propose anhedonia reflects abnormalities in the temporal dynamics of positive emotion in schizophrenia, characterized by intact consummatory and impaired anticipatory pleasure. A comprehensive meta-analysis can directly test this theory using self-report data. Method: A meta-analysis was performed on studies reporting Temporal Experience of Pleasure Scale (TEPS) data from healthy controls and schizophrenia or schizotypy groups. The TEPS was examined as it contains subscales to measure both consummatory and anticipatory pleasure separately. Statistical heterogeneity and study bias were examined. Meta-regressions evaluated moderators. Results: 53 studies were retrieved (7, 797 participants). Results revealed small effect sizes for comparisons of combined schizophrenia/schizotypy and control groups for both consummatory and anticipatory pleasure. Within-group comparisons of pleasure conditions were nonsignificant. The percentage of male schizophrenia/schizotypy participants significantly moderated anticipatory and consummatory pleasure for the combined sample and schizotypy alone; male participants were found to report reduced pleasure. There was only minor evidence of bias; sensitivity analysis confirmed result robustness. Exploratory outlier removal for schizophrenia within-group pleasure comparisons revealed a statistically significant difference between reported anticipatory and consummatory pleasure, with consummatory pleasure reduced relative to anticipatory (i.e., in the opposite direction of the majority of experimental research findings). Conclusions: These findings provided only modest support for the temporal dynamics of positive emotion conceptualization because they revealed no evidence for: 1) specific anticipatory pleasure deficits in schizophrenia-spectrum participants compared to controls; 2) significant reductions in anticipatory pleasure relative to consummatory pleasure in schizophrenia-spectrum participants.